The Effectiveness of Standardized Patient Experience (SPE) Model in Teaching Critical Thinking Capability of Bachelor Nursing Students Compared to Case Study - Ryan Hara Permana (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2016)
Critical thinking is a main ability for nurses. However, the learning methods that are usually used by nursing education institutions cannot facilitate the development of critical thinking of nursing students optimally. This research investigated the effectiveness of Standardized Patient Experience (SPE) model in practicing the critical thinking capability of nursing students compared to case study. This quasi-experiment study used 77 nursing students as the samples that were divided into control and experiment group. Although there are no significant different between the total critical thinking scores of the students who participated in SPE compared to case study (p= 0.146), but there are differences in analysis and problem solving aspect (p==0.019 and 0.00). the satisfaction and confidence level of the students toward the SPE are also significantly increased compared to case study (p=0.01 dan p=0.00). To conclude, both the SPE and case study method are effective in developing the critical thinking of the nursing students.